PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS FLIP CHART PADA MATERI RHIZOPHORA UNTUK SISWA SMAN TAEKAS - Febronius Ardian Baun; Vinsensia Ulia Rita Sila; Muhammad Amran Shidik (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
The research on the development of flip chart-based learning media is motivated by the problems that students get during the biology learning process, especially in the kingdom plantae material, namely the difficulty of identifying, finding and memorizing the scientific names of these plants. From the results of initial observations made with biology subject teachers stated that the teacher strongly agreed with the development of new, simple and effective learning media so that they could overcome the difficulties experienced by students during the learning process, such as flip media charts. The method in this research is Research & Development (R&D). The results of research of the media expert’s assessment obtained an average value of 88.42%, including the